Extravillous trophoblast invasion and decidualization in cesarean scar pregnancies - Lufen Gao; Hui Chen; Jing Liu; Minghua Wang; Fangfang Lin; Guang Yang; Gendie E. Lash; Ping Li (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The increasing cesarean section rate has led to an increase in the number of subsequent pregnancies resulting in a cesarean scar pregnancy. There appears to be preferential attachment of the blastocyst to the scar site, which may be associated with defective decidua in that region, resulting in abnormal implantation, which can in turn negatively affect the success of the pregnancy. The aim of the current study was to evaluate the extravillous trophoblast, decidua, and myometrium in scar and adjacent non‐scar regions of the implantation site of a cesarean scar pregnancy. Material and Methods Samples containing a gestational mass were obtained by laparoscopic excision from patients with a cesarean scar pregnancy at 6–11 weeks of gestation as diagnosed by transvaginal or transabdominal ultrasound (n = 8 type II cesarean scar pregnancy). Cesarean scar pregnancy tissues were separated into scar and non‐scar regions, and the scar regions were sub‐separated into non‐implantation and implantation sites. Serial sections were histologically examined after hematoxylin and eosin, Masson's trichrome and immunochemical staining, and changes in the myometrium, extravillous trophoblast, and decidua were evaluated. Results In cesarean scar pregnancy, compared with scars not in the implantation site, scars in the implantation site displayed increased fibrosis, and had disrupted myometrium, which was related to varying patterns of E‐cadherin expression as a response to extravillous trophoblast invasion. In addition, local decidua was found at the non‐scar implantation sites, with multinucleated trophoblast giant cell accumulation and shallow invasion. These features were not evident in the scar implantation sites. Conclusions This study emphasizes that the decidua drives multinucleated trophoblast giant cell differentiation, limiting the degree of invasion. Better characterization of this differentiation process may be helpful for better management and avoidance of the consequences of cesarean scar pregnancy.